Enhancing Students’ Ability to Write Professional Emails for Office Communication through Guided Practice: A Classroom-Based Study - Fitria Wahyu Nugraheni (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study seeks to explore the application of guided practice in instructing professional email composition for office communication and to assess its effect on students' writing proficiency. This study utilised a qualitative descriptive design inside a classroom setting, supplemented by quantitative data. The participants were secretary students engaged in an English course centred on office communication. The data were gathered via classroom observation, writing assignments (pre-test and post-test), and student reflection surveys. The findings reveal that guided practice was effectively implemented through structured stages, including modeling, guided exercises, feedback, and revision. The results also indicate a significant improvement in students’ writing ability, particularly in terms of organization, language use, and the use of appropriate tone and politeness. In addition, students showed positive responses toward the use of guided practice, as it helped them better understand the structure and conventions of professional email writing and increased their confidence. In conclusion, guided practice is an effective instructional strategy for improving students’ professional email writing skills. It is recommended for use in English for Specific Purposes (ESP) contexts, particularly in preparing students for workplace communication.